A comparative study of the reactivity of anti-HIV sera with native, synthetic and recombinant antigens derived from the envelope gene of HIV-1 - Eekhout, Tonia (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.(Med.)) -- University of Stellenbosch, 1994.